Penerapan Etika Berbisnis dalam Operasional Usaha Pelaku UMKM Didesa Malaju, Kecematan Kilo, Kabupaten Dompu - Muhammad Yusuf; Ibril Umar Batistuta; Fitratul Aqidah; Tri Wulandari; Nurhasanah (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
In doing business, both large and small businesses need to pay attention to business ethics. Ethics is behavior that a person carries out morally in accordance with applicable norms. Bu Marifa umkm is an umkm that operates in the field of food production in the form of sea products, umkm ibu marifa is located in West Paropa hamlet, malaju village, kilo subdistrict, dompu district. It is necessary to apply ethics in doing business with the method offered to partners/MSMEs in the form of education/socialization using LEAFLET which is carried out door to door. . The material provided in the leaflet includes a discussion of (1) The role of ethics in business for MSMEs, (2) Benefits of doing business for MSMEs (3) Application of ethical principles in business in financial, marketing, production and HR activities. The results of the activity showed that partners were very enthusiastic in listening and discussing during the activity. Apart from that, it can provide knowledge about ethics in running a business.